2020
DOI: 10.1002/mrd.23423
|View full text |Cite
|
Sign up to set email alerts
|

Wingless ligands and beta‐catenin expression in the rat endometrium: The role of Wnt3 and Wnt7a/beta‐catenin pathway at the embryo–uterine interface

Abstract: Wnt/beta-catenin signaling may play an essential role in endometrial decidualization, placentation, and the establishment of pregnancy. We investigate here the possible roles, immunolocalizations, and synthesis of the Wnt3, Wnt7a, and betacatenin proteins in the rat endometrium during the estrous cycle and early postimplantation period. Wnt3 and Wnt7a had a similar localization and dynamic expression relative to the endometrial stages. Wnt7a immunostaining was not limited only to the luminal epithelial cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…WNT3 also plays an important role in embryonic development and regulates trophectoderm differentiation in blastocysts [35]. Kaloglu C et al found that WNT3 is involved in regulating decidualization, stromal cell proliferation and trophoblast cell in ltration in the rat uterus [36]. In the present study, we found that the promoter region of WNT3 was hypomethylated and that its expression was increased in preeclamptic placentas.…”
Section: Discussionsupporting
confidence: 57%
“…WNT3 also plays an important role in embryonic development and regulates trophectoderm differentiation in blastocysts [35]. Kaloglu C et al found that WNT3 is involved in regulating decidualization, stromal cell proliferation and trophoblast cell in ltration in the rat uterus [36]. In the present study, we found that the promoter region of WNT3 was hypomethylated and that its expression was increased in preeclamptic placentas.…”
Section: Discussionsupporting
confidence: 57%
“…WNT3 also plays an important role in embryonic development and regulates trophectoderm differentiation in blastocysts [ 35 ]. Kaloglu C et al found that WNT3 is involved in regulating decidualization, stromal cell proliferation, and trophoblast cell infiltration in the rat uterus [ 36 ]. In the present study, we found that the promoter region of WNT3 was hypomethylated and that its expression was increased in preeclamptic placentas.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, several WNT family genes were identified to be associated with reproduction traits in American mink, including WNT3 and WNT9B (both found within the duplication CNVR118), and WNT3A (overlapped with the deletion CNVR23). It is well-documented that the expression of WNT3 during the early pregnancy mediates the stromal cell proliferation and trophoblast invasion, eventually affecting the embryonic development 86 . Comparably, the WNT9B gene has been reported as one of the key genes associated with inducing the gonadotropin-releasing hormone secretion during follicular development in sheep 87 .…”
Section: Discussionmentioning
confidence: 99%